The second life of polymyxins - Ageevets V.A. (Клиническая микробиология и антимикробная химиотерапия, 2024)
Polymyxins are a well-known class of antimicrobial agents that have been used in clinical practice since the 1950s but lost their clinical significance for several decades. The rise of antibiotic resistance has led to the resurgence of polymyxins in practice and triggered an "explosive growth" in their use for treating hospital-acquired infections caused by carbapenem-resistant Gram-negative bacteria. This review provides a characterization of polymyxins, results from clinical studies, and defines the role of polymyxin B and colistin in the therapy of patients with severe infections considering current data on pathogen susceptibility in Russia and relevant clinical guidelines.